Protease FRET reporters targeting neutrophil extracellular traps - Guerra, Matteo; Halls, Victoria S.; Schatterny, Jolanthe; Hagner, Matthias; Mall, Marcus A.; Schultz, Carsten (Journal of the American Chemical Society, 2020)
Neutrophil extracellular traps (NETs) consist of DNA released by terminally stimulated neutrophils. They fine-tune inflammation, kill pathogens, activate macrophages, contribute to airway mucus obstruction in cystic fibrosis, and facilitate tumor metastasis after dormancy. Neutrophil proteases such as elastase (NE) and cathepsin G (CG) attach to NETs and contribute to the diverse immune outcome. However, because of the lack of suitable tools, little spatiotemporal information on protease activities on NETs is available in a pathophysiological context to date. Here, we present H-NE and H-CG, two FRET-based reporters armed with a DNA minor groove binder, which monitor DNA-bound NE and CG activity, respectively. The probes revealed that only NE maintains its catalytic ability when localized to DNA. Further, we demonstrated elevated protease activity within the extracellular DNA of sputum from cystic fibrosis patients. Finally, H-NE showed NE activity at single-cell and free DNA resolution within mouse lung slices, a difficult to achieve task with available substrate-based reporters.
Gesehen am 18.04.2022